Desenvolvimento e testes de um dessalinizador solar com pré-aquecimento de água - Luna, Flávio Melo de (2016)
In the Brazilian semi-arid region, there is a strong need to have drinking water taken from the brackish water of existing wells, due to the successive droughts in this region. The purpose of this work was to study alternative materials, to measure and test a prototype for an active solar desalination unit with a collector built with masonry and ferro-cement, and to produce desalinated water from brackish water. The dimensioned active desalinator consists of a flat solar collector using 50 m of a spiral polyethylene hose for the preheating of brackish water at temperatures up to 90 ºC and an evaporation and condensation chamber (heat exchanger) that receives the preheated water from the solar collector where the boiling desalination process takes place. The tests were carried out in the city of João Pessoa (Latitude: 07º06'54"S Longitude: 34º51'47"W) in Paraíba, where measurements and comparisons of the temperatures inside and outside the prototype were made. The radiation of the place and the amount of desalinated water produced were also measured every day. During the testing period, an average of 3.3 liters per squared meter of desalinated water was produced daily. Thus, solar energy as an alternative energy source was able to promote water heating and desalination with great advantages for the families of the brazilian northeastern semi-arid region, given their difficulty of access to drinking water. In addition to this, the alternative materials proposed in the desalination unit and solar collector have been proven effective for water desalination.